ChemInform Abstract: Hydrothermal Synthesis, Crystal Structures and Characterization of New Vanadoborates: The Novel Decorated Cage Cluster [V6B22O44(OH)10]. Issue 27 (13th June 2013) - Liu, Xing; Zhou, Jian; An, Litao; Chen, Rong; Hu, Feilong; Tang, Qiuling
Abstract The crystal structures of the new compounds (III), (IV), and (V) are determined by single crystal XRD.